E-Zakat: Breakthroughs and Innovations in Information Technology in Increasing Zakat Receipts in Indonesia - Dini Vientiany; Faisar Ananda Arfa; Dede Ruslan (International Journal of Artificial Intelligence Research, 2022)
Zakat is one of the obligations that need to be carried out by Muslims. Baznas has made significant advancements and advances in the zakat program through the use of digital technology, such as online zakat payments. It is the goal of this research to determine whether or not the digital zakat system's installation and impact on Baznas's acceptance of zakat funds. As a result of the study, Baznas and muzakki can save time and money by digitizing zakat and using it to collect zakat funds digitally. The collecting of zakat funds should also be made more open to the public, transparent, enormous, and effective. Through bank transfers, websites, QR code scans, and social media, Baznas aims to digitize zakat. Due to lack of socialization and promotion by Baznas to the community and some people's unwillingness to pay their zakat digitally, the community hasn't felt the full impact of the digitalization system from its website and QR code.